ANALISIS ARUS KAS DAN ANGGARAN KAS PADA PT. PLN (Persero) AREA MAKASSAR - Silvister Saman (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
This study aims to find out the difference between the cash budget with cash realization of the operation of the company's operations in each budget period. The method of analysis used in this research is the analysis of variance, ie comparing planned and actual cash from all the company's activities in the cash flow statement rupiah unit and percentage. While the results of the discussion of this study were (1) to three (3) years PT. PLN (Persero) Makassar Area still able to increase its main revenue sales revenue of electricity which each year is increasing, although not able to cover the operating expenses, due to lack of power users outside peak load so that the company still gets droping the operating costs of the central office. (2) Budget cash flow/cash flow contains estimates and projections of the future, and record cash flow/cash flow last year to provide information about management in the past. Projected cash flow (cash flow) is useful for estimating the timing and amount of new loans were required during the year and the time and the amount of loan repayment or plan.